Long‐Term Stability of the Oxidized Hole‐Transporting Materials used in Perovskite Solar Cells. Issue 39 (19th June 2018) - Kasparavicius, Ernestas; Magomedov, Artiom; Malinauskas, Tadas; Getautis, Vytautas
Abstract: The vast majority of the hole transporting materials require the use of chemical doping as an essential step for preparation of efficient perovskite solar cells. An oxidized organic hole‐transporting material, obtained during a doping procedure, could potentially be one of the weak links in the device composition. It is not uncommon for the solar cell to heat up under summer sun; therefore, all device components must possess some degree of resistance to repetitive thermal stress. In the current publication, a series of oxidized hole‐transporting materials have been synthesized and their long‐term stability investigated. During thermal stability testing of the films, kept at 100 °C under an inert atmosphere, it was observed that oxidized HTMs start to degrade and partly revert to original unoxidized material. It is known that oxidized HTM, formed during doping, is responsible for the increased conductivity and ultimately for better efficiency of hole extraction process in the PSC device; therefore, observed instability of the oxidized HTMs in the thin films at elevated temperatures could be one of the causes of drop in conductivity reported for the doped spiro‐OMeTAD. It could also potentially be one of the reasons why perovskite solar cells lose their efficiency under prolonged thermal stress. Abstract : An oxidized hole transporting material, formed during doping, is responsible for increased conductivity and better efficiency of hole extraction process in perovskite solar cells. During long‐term thermal stability testing, degradation and reversion back to original unoxidized material was observed. Reported instability could be one of the causes of drop in hole transporting material's conductivity and ultimately in device's performance.